ZORA NEALE HURSTON: Writing Culture - Mason-Grant, Joan (Culture, 1990)
The life-work of novelist/essayist/folklorist Zora Neale Hurston has been recently and lovingly salvaged from the black hole of literary oblivion. This reclamation occurs during a time of increasing attention paid to marginalia within various discourses of theory. This theoretical and historical coincidence has inspired me to question the continued relegation of Hurston’s life-work to the realm of “the literary” and the virtual absence of any serious exploration of its anthropological significance. In this study, therefore, I turn to Hurston as a writer of culture. I argue that Hurston’s work exemplifies the increasingly complex contemporary “field” in which anthropologists write culture, and thus animates the contemporary rethinking underway regarding the process, product and status of ethnographic writing. Her writing of culture weaves intriguingly back and forth over the boundaries of fiction and non-fiction, white culture and black culture, wealthy urban class and poor rural class, and, perhaps most interestingly, ‘subject’–anthropologist and ‘object’-culture. In tracing the sense in which Hurstons’s work continuously problematizes such simple we-they oppositions and the search for a singular voice, I argue that the theoretical insights of deconstruction take us a long way in understanding the politics of representation at work in Hurston’s heterogeneous texts, and help us to rethink their status as ‘representational’.